Exploring the impact of the care sport connector in the Netherlands - Karlijn E. F. Leenaars; Eva Smit; Annemarie Wagemakers; Gerard R. M. Molleman; Maria A. Koelen (BMC, 2017)
Abstract Background Regular physical activity (PA) is deemed to contribute to the primary and secondary prevention of several chronic diseases, like diabetes mellitus, cancer, cardiovascular diseases, and osteoporosis. In 2012, Care Sport Connectors (CSC), to whom a broker has been ascribed, were introduced in the Netherlands to stimulate PA and guide primary care patients towards local sport facilities. The aim of this study was to explore which structural embedding is the most promising for CSCs' work. Methods In three rounds of interviews, 13 CSCs were followed for 2 years in their work. In these interviews, a network survey was used to identify organisations in the CSCs' network, whether they collaborated with these organisations, and the role of the organisations in the connection. Data from the network survey were analysed using the RE-AIM framework and disaggregated into how CSCs were structurally embedded (Type A: only PA sector; Type B: different sectors; Type C: partnership). A related samples Wilcoxon signed rank test was performed to study how the CSCs' network developed between 2014 and 2016. Results All CSCs established a connection between the primary care and the PA sector in which the average number of organisations with which CSCs collaborated increased significantly between 2014 (8.3) and 2016 (19.8) (p = 0.002). However, differences were identified in the way CSCs were structurally embedded and in the way they established the connection. Type A CSCs established the connection mostly around their own activities, supported PA organisations with their activities, and collaborated with primary care and welfare professionals around their own activities. Type B and Type C CSCs established the connection by organising, supporting, and implementing different kinds of activities targeting different kinds of audiences, and collaborated mostly with primary care professionals around the referral of professionals' patients. Conclusions The results of this study suggest that adopting an integral approach (Type B and C) for the structural embedding of the CSC is more promising for reaching the desired outcomes. Whether CSCs really improve the target groups' PA level and health needs to be further studied. Trial registration Dutch Trial Register NTR4986 . Registered 14 December 2014.